Gender and Hemispheric Asymmetries in Acquired Sociopathy - de Oliveira-Souza, Ricardo; Paranhos, Thiago; Moll, Jorge; Grafman, Jordan (Frontiers in Psychology, 2019)
The emergence of enduring antisocial personality changes in previously normal individuals, or “acquired sociopathy”, has consistently been reported in patients with bilateral injuries of the ventromedial prefrontal cortex. Over the past three decades, cases of acquired sociopathy with (a) bilateral or (b) unilateral sparing of the ventromedial prefrontal cortex have been reported. These cases indicate that at least in a few individuals (a’) neural structures beyond the ventromedial prefrontal cortex are also critical for normal social behavior, and (b’) the neural underpinnings of social cognition may be lateralized to one cerebral hemisphere. Moreover, researchers have presented evidence that lesion laterality and gender may interact in the production of acquired sociopathy. In the present review, we carried out a comprehensive literature survey seeking possible interactions between gender and hemispheric asymmetry in acquired sociopathy. We found 85 cases of acquired sociopathy due to bilateral (N = 48) and unilateral (N = 37) hemispheric injuries. A significant association between acquired sociopathy and right hemisphere damage was found in men, whereas lesions were bilateral in most women with acquired sociopathy. The present survey shows that: (i) the number of well-documented single-cases of acquired sociopathy is surprisingly small given the length of the historical record; (ii) acquired sociopathy was significantly more frequent in men after an injury of the right or of both cerebral hemispheres; and (iii) in most women who developed acquired sociopathy the injuries affected both cerebral hemispheres. These findings may be especially valuable to neuroscientists and to functional neurosurgeons in particular for the planning of tumor resections as well as for the choice of the best targets for therapeutic neuromodulation.